2015
DOI: 10.4149/neo_2015_037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of risk factors on prevalence of anal HPV infection in women with simultaneous cervical lesion

Abstract: The aim of our study was to determine the risk factors associated with anal HPV infection in HIV-negative women with high-grade cervical lesion. The study group included 172 "high-risk" women who underwent conization for high-grade cervical intraepithelial lesion or microinvasive cervical cancer (CIN 2+). The control group consisted of 100 "low-risk" women with non-neoplastic gynecologic diseases. All participants completed a questionnaire detailing medical history and sexual risk factors and were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 18 publications
3
24
0
1
Order By: Relevance
“…Most experts recommend anal screening for HIV+ men and women as well as men who have sex with men [3], and the American Cancer Society suggests that those at increased risk of anal intraepithelial neoplasia (AIN) may benefit from screening, including women who have had cervical or vulvar cancer [4]. A recent study by Slama, et al examined 172 high-risk women with cervical intraepithelial neoplasia 2 or greater (CIN2+) compared to 100 women with non-neoplastic gynecologic disease [5]. They found that concurrent cervical and anal HPV infection was found in 42% of the high-risk women vs. 8% of controls.…”
Section: Introductionmentioning
confidence: 99%
“…Most experts recommend anal screening for HIV+ men and women as well as men who have sex with men [3], and the American Cancer Society suggests that those at increased risk of anal intraepithelial neoplasia (AIN) may benefit from screening, including women who have had cervical or vulvar cancer [4]. A recent study by Slama, et al examined 172 high-risk women with cervical intraepithelial neoplasia 2 or greater (CIN2+) compared to 100 women with non-neoplastic gynecologic disease [5]. They found that concurrent cervical and anal HPV infection was found in 42% of the high-risk women vs. 8% of controls.…”
Section: Introductionmentioning
confidence: 99%
“…On analysing the combinations of viruses pertaining to the species 16 and 18, we observed that up to 50% of the study participants were infected by the viral species HPV16 and 37% by the species HPV18. HPV16 is the genotype that has been shown most frequently, in the majority of published studies, to be associated with ano-genital pathology in both genders [37, 38]. HIV infection is among the associated risk factors in MSM patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that HPV infection is an important cause of cervical cancer (5,6). HPVs are commonly divided into high-risk and low-risk types, with the high-risk type HPV 16 representing the predominant type associated with cervical cancer (7).…”
Section: Introductionmentioning
confidence: 99%